2010
DOI: 10.1002/bit.22926
|View full text |Cite
|
Sign up to set email alerts
|

Reaction–diffusion constraints in living tissue: Effectiveness factors in skeletal muscle design

Abstract: A mathematical model was developed to analyze the effects of intracellular diffusion of O(2) and high-energy phosphate metabolites on aerobic energy metabolism in skeletal muscle. We tested the hypotheses that in a range of muscle fibers from different species (1) aerobic metabolism was not diffusion limited and (2) that fibers had a combination of rate and fiber size that placed them at the brink of substantial diffusion limitation. A simplified chemical reaction rate law for mitochondrial oxidative phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 51 publications
(65 reference statements)
1
24
0
1
Order By: Relevance
“…In support of this view, shifts in mitochondrial distribution toward the fiber periphery during hypertrophic fiber growth in a variety of comparative models appear to be independent of opposing shifts in nuclear distribution toward the fiber center (Nyack et al, 2007;Hardy et al, 2009;Hardy et al, 2010;Priester et al, 2011), and experiments with isolated cells indicate that mitochondrial DNA replication is independent of proximity to nuclei (Magnusson et al, 2003). Moreover, reactiondiffusion models indicate that spatial gradients in high-energy phosphate molecules like AMP are very slight in muscle (Jimenez et al, 2008;Dasika et al, 2011;Pathi et al, 2011), and we know of no biogenesis signals that vary spatially across the radius of the fiber. In contrast, as mentioned above, mitochondrial degradation is a regionally variable, selective process, whereby damaged mitochondria are specifically targeted and removed.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…In support of this view, shifts in mitochondrial distribution toward the fiber periphery during hypertrophic fiber growth in a variety of comparative models appear to be independent of opposing shifts in nuclear distribution toward the fiber center (Nyack et al, 2007;Hardy et al, 2009;Hardy et al, 2010;Priester et al, 2011), and experiments with isolated cells indicate that mitochondrial DNA replication is independent of proximity to nuclei (Magnusson et al, 2003). Moreover, reactiondiffusion models indicate that spatial gradients in high-energy phosphate molecules like AMP are very slight in muscle (Jimenez et al, 2008;Dasika et al, 2011;Pathi et al, 2011), and we know of no biogenesis signals that vary spatially across the radius of the fiber. In contrast, as mentioned above, mitochondrial degradation is a regionally variable, selective process, whereby damaged mitochondria are specifically targeted and removed.…”
Section: Introductionmentioning
confidence: 86%
“…The full model of Beard (Beard, 2005) is too computationally intensive to apply to our population of mitochondria. Therefore, Dasika et al (Dasika et al, 2011) developed a rate law that closely approximates the full model of Beard (Beard, 2005) that expresses ATP production in the mitochondria as a function of the concentration of oxygen, ADP and inorganic phosphate (P i ). This rate law was used to describe reactions in the mitochondria.…”
Section: Model Formulation Reactions and Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that leaflets exist on the verge of core hypoxia because of their lack of vascularization,10 and that leaflet motion including coaptation helps to convectively deliver nutrients to the deeper regions of valves 11, 12. Indeed, human valves are in the 300‐ to 700‐μm thickness range,13 beyond the theoretical passive oxygen diffusion range of 100 μm14 when unloaded, yet remain fully viable. Of note, AV area increases at least 20% to 30% at coaptation 15.…”
Section: Discussionmentioning
confidence: 99%